De la production paysagère à la formation des paysages vécus à Conakry (Guinée) - Julie Gangneux-Kebe (Projets de Paysage)
In Conakry, a capital city shaped ex nihilo, pre-colonial landscapes within the city were erased. At the end of the nineteenth century, the colonial administration designed and created landscapes which, at the time of Independence gave way to new social and political representations of urban landscapes which corresponded to the successive political regimes. Although such a shaping of landscapes was replaced by urban planning through "management and infrastructure", there remained here and there landscapes shaped by the know-how of the inhabitants and by forms of socio-ecological mutual aid enabling them to live in such a hot climate. This article proposes to take a closer look at these diverse and changing lifestyles practised on a micro scale in the working-class neighbourhoods of the Guinean capital in order to identify new possibilities in landscape design and planning in the tropics.